Distribution of psychological types in urban adolescents (on the example of Kharkiv District) - Etkalo, K.; Atramentova, L. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
The materials of anonymous testing of 530 students in grades 9‒11 of six Kharkiv secondary schools, including general education, sports, gymnasiums, and a school with in-depth study of a foreign language, have been analyzed. In total, 252 boys and 278 girls aged 14‒17 years were examined. Eysenck personality questionnaire (EPQ) was used to determine the temperament type taking into account introversion and/or extraversion of the personality, as well as emotional stability. A proportion of various temperament types (sanguine, phlegmatic, choleric, and melancholic) and the indices of introversion, extraversion and ambiversion were calculated. The material was analyzed separately for each school, as well as for the Kharkiv population as a whole. The results are presented as percentages with 95 % confidence intervals. The girls showed a greater interest in the study, 43 % of them agreed to participate in the questionnaire, while only 38 % of the boys agreed to take the test. Analysis of the personal characteristics distribution within the different schools revealed a wide variation range. The proportion of psychological types of boys in various schools changed as follows: sanguine persons from 14.7 to 53.8 %, phlegmatic persons from 10.2 to 25.3 %, choleric persons from 7.7 to 38.3 %, melancholic persons from 9.5 to 23.5 %, introverts from 14.7 to 36.0 %, extroverts from 8.8 to 55.1 %, and ambiverts from 28.6 to 76.5 %. The psychotype proportion among girls was also variable. The small sample size did not allow us to draw a conclusion about the significance of differences between schools in any psychological characteristics, thus, we could not associate them with the school specialization. To increase statistical power, the data were pooled and the results were presented as population indices. The distribution of personal characteristics in boys and girls was as follows: sanguine persons 31.0 and 19.8 %, phlegmatic persons 21.0 and 19.4 %, choleric persons 27.0 and 44.2 %, melancholic persons 21.0 and 16.6 %, introverts 23.8 and 19.8 %, extroverts 32.1 and 36.0 %, ambiverts 44.1 and 44.2 %. Statistically significant gender differences were found for choleric and sanguine temperaments.